High flexural strength lightweight fly ash geopolymer mortar containing waste ﬁber cement - Sakchai Naenudon; Anousit Vilaivong; Yuwadee Zaetang; Weerachart Tangchirapat; Ampol Wongsa; Vanchai Sata; Prinya Chindaprasirt (Case Studies in Construction Materials, 2022)
This study aims to investigate the use of waste fiber cement (WFC) in making high flexural strength lightweight fly ash geopolymer mortar. The WFC was crushed and passed a No. 4 sieve (particle size of 0.12–4.75 mm) for use as a fine aggregate with a low bulk density of 1124 kg/m3. It was used to replace river sand at 0–40% by volume for making geopolymer mortar with alkaline solution to fly ash ratio of 0.7 and sodium hydroxide to sodium silicate ratio of 1.0. Their properties were tested and compared with those of Portland cement mortars. The results indicated that the workability, density, and strength of mortars decreased with an increase in WFC contents. The geopolymer mortars with 30% WFC had a density of 1789 kg/m3, compressive strength of 17.7 MPa, and high flexural strength of 3.4 MPa. With higher WFC content of 40%, the density and compressive strength were reduced to 1750 kg/m3 and 13.3 MPa, respectively, with the flexural strength of 2.8 MPa. The incorporation of 30–40% WFC resulted in the lightweight mortar with a very high flexural strength of around 20% of compressive strength. Furthermore, the use of WFC as recycled aggregate in the geopolymer-based system exhibited better thermal insulation, sound absorption, and acid resistance than in the Portland cement-based system. The developed geopolymer mortars containing WFC in this study were appropriate for use as lightweight mortars with thermal and sound insulating properties.